THE INFLUENCE OF ORGANIZATIONAL CULTURE, ORGANIZATIONAL COMMITMENT, AND LEADERSHIP ON EMPLOYEE PERFORMANCE AT PT URCHINDIZE INDONESIA: PENGARUH BUDAYA ORGANISASI, KOMITMEN ORGANISASI, DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT URCHINDIZE INDONESIA - Muhammad Isnan Ronaldi; Fu’ad, Eko Nur (SEGMEN Jurnal Manajemen dan Bisnis, 2025)
This study aims to examine the effect of organizational culture, organizational commitment, and leadership on employee performance at PT Urchindize Indonesia. This study involved a population of 150 people, where sampling was carried out using the saturated sample method. However, of the total 150 questionnaires distributed to the population, only 109 questionnaires were returned completely and validly by the respondents. A total of 41 members of the population did not respond due to several reasons, such as busyness, or unwillingness to participate. The data collection method uses a questionnaire with the type of research data used in this researcher is primary then the data is analyzed using Partial Least Square (PLS) which is processed with SmartPLS 3.0. The results showed that the variables of organizational culture, organizational commitment, and leadership had a significant positive effect on employee performance at PT Urchindize Indonesia.Keywords: Organizational Culture, Organizational Commitment, Leadership, Employee Performance